2013
DOI: 10.1016/j.atmosenv.2013.01.042
|View full text |Cite
|
Sign up to set email alerts
|

Aeolian dust as a transport hazard

Abstract: The effects of blowing dust on transport operations are often mentioned as one of the significant impacts of aeolian processes on human welfare. However, few studies have been presented to demonstrate this impact. This research examined official air traffic incident reports in Australia for inclusively 1969-2010 to characterize the hazard of blowing dust to aviation in the country, the first such study of its kind. For the 42 year record, 61 incidents were identified (mean 1.4 per annum), with the large majori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 27 publications
(26 reference statements)
0
24
0
Order By: Relevance
“…In a national study using reports of air traffic incidents in Australia, Baddock et al () concluded that atmospheric dust in the country represents at worst an inconvenience and an economic cost; nearly two thirds of the dust‐caused air safety issues identified related to navigational problems. There were no reported deaths during the 42‐year period studied (1969–2010) and these authors pointed out that improvements in aviation technology were at least partly responsible for a reduction in incidents in more recent decades.…”
Section: Transport Sectormentioning
confidence: 99%
See 1 more Smart Citation
“…In a national study using reports of air traffic incidents in Australia, Baddock et al () concluded that atmospheric dust in the country represents at worst an inconvenience and an economic cost; nearly two thirds of the dust‐caused air safety issues identified related to navigational problems. There were no reported deaths during the 42‐year period studied (1969–2010) and these authors pointed out that improvements in aviation technology were at least partly responsible for a reduction in incidents in more recent decades.…”
Section: Transport Sectormentioning
confidence: 99%
“…These happenings represent a significant hazard not only to the inhabitants of dryland regions (Middleton and Sternberg, 2013), but also to the many people who live outside of them because desert dust haze frequently is transported great distances (Kellogg and Griffin, 2006). The consequences for human society are varied and wide-ranging, including threats to health (Zhang et al, 2016), agriculture (Phillips, 1999), electricity generation (Mani and Pillai, 2010), and the transport industry (Baddock et al, 2013). To provide a perspective on the impacts of SDS on society and as a natural hazard, research on hospitals in Iran ranked the importance of 10 hazards and their effects: earthquake (71 per cent); extreme temperature (64 per cent); dust storm (59 per cent); hospital overload (48 per cent); power outage (48 per cent); water cut (shortage) (46 per cent); fire (45 per cent); torrential rain (45 per cent); storm (43 per cent); and landslide (39 per cent) (Ardalan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Others interesting aspects are that mineral aerosols exert an important influence over the distribution of soil nutrients (Mahowald et al, 2005;Yoon et al, 2007), induce changes in soil characteristics (McTainsh and Strong, 2007) and cause adverse effects on human health (Boreson et al, 2004;Fisher et al, 2000;Goudie, 2009;De Longueville et al, 2010. Additionally, large concentrations of aeolian emissions could lead to problems in transport operations (Baddock et al, 2013). Mineral dust deposition on the ocean surface represents an input of micronutrients and, as a consequence, partially controls the productivity of marine ecosystems (Shi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Windblown dust can impair visibility for drivers, which can then lead to increased accident risks (Ashley et al, 2015;Goudie, 2014;Okin et al, 2011). While studies of the large-scale effects of dust in the Western United States often focus on wind erosion of surface soil and long-range transport of dust and its effects on Earth processes (e.g., Neff et al, 2008;Painter et al, 2010), there are few studies that focus on dust emitted from local dust sources that could create hazardous travel conditions (e.g., Baddock et al, 2013;Li et al, 2017). Dust-caused traffic accidents can be large and deadly.…”
Section: Introductionmentioning
confidence: 99%